Tinjauan Yuridis Pelaksanaan Pendaftaran Tanah Secara Elektronik Berdasarkan Permen ATR/Kepala BPN RI No. 3 Tahun 2023 tentang Penerbitan Dokumen Elektronik dalam Kegiatan Pendaftaran Tanah - Riyanto, Tabah; Suardi; Martin, Abraham Yazdi (Neolectura, 2025)
This research examines the implementation of electronic land registration based on the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency No. 3 Year 2023 which aims to transform the land administration process in Indonesia. In this digital era, electronic land certificates are introduced as an alternative to physical certificates to provide efficiency, ease of access, and legal protection for landowners. The problems in this research include the implementation of the electronic certificate system and legal protection for land rights holders. Through a qualitative method with a normative juridical approach, this study found that although the electronic system has the potential to increase legal certainty and security of land administration, there are obstacles in its implementation, such as infrastructure readiness, data security, and public understanding. Recommendations include improving digital infrastructure, socialising to the public, and strengthening supervision and data security to strengthen legal protection for rights holders. With proper mitigation, electronic certificates can provide significant benefits in land management in Indonesia.